PUBLIC POLICIES AND THE NATIONAL ENVIRONMENT SYSTEM (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This work aims to highlight the responsibility of the Public Power in effective public policies, as well as conceptualize it and list its importance for society in preserving the environment for future generations. Having the National Environment System (SISNAMA), a fundamental role in the protection of the environment through the creation of normal, inspection, licensing and environmental studies.The relevance of this study has a social character, since the discussion on that topic is essential and necessary for the visualization and understanding of the factors that can cause negative impacts to the environment, in addition to educational practices for the preservation of the environment for the present and future generations, guided by the values ​​of preservation, caution and respect for the community.The hypothetical-deductive method was used to obtain the conclusions, using legal material, from books, scientific articles, legislation and online sites that were analyzed in the elaboration of the research